Estudio preliminar de la composición química y de las inclusiones fluidas en fluoritas hidrotermales de la Sierra de Ancasti, Catamarca, Argentina - Iriarte, Matías Ernesto (2019)
Preliminary study of chemical composition and fluid inclusions in hydrothermal fluorites from Ancasti range, Catamarca, Argentina. In this paper, a preliminary study about the petrography and thermometric data of fluid inclusions and REE-composition from hydrothermal fluorite veins from northwestern region of the Ancasti range, Catamarca province (Argentina) is presented. The fluorite of the veins is accompanied by quartz and chalcedony. The veins are hosted by Upper Devonian-Lower Carboniferous granitoids. The fluid inclusions study was carried out in granular purple fluorite while the REE-composition was obtained in five fluorite-samples of three different veins. The fluid inclusions are variable in size and shape. They are predominantly biphasic (liquid and gas phases) and the average homogenization temperature is 126ºC. The REE geochemistry shows a total content that varies from 6.70 to 64.33 ppm (average 25.51 ppm). The LREE/HREE relationship is generally greater than 1 and Eu/Eu* ratio varies between 0.66 and 0.81. The diagram Tb/Ca vs Tb/La in accordance with geological setting and textural-mineralogical features indicate a hydrothermal origin for these deposits. Additionally, these textures show more than one mineralizing pulse and low formation temperaturas.